Saponins: Advances in extraction techniques, functional properties, and industrial applications - Summaia Fordos; Sana Amin; Namrah Abid; Imran Pasha; Muhammad Kashif Iqbal Khan; Amina Amin; Muhammad Gulzar; Muhammad Subtain; Gholamreza Abdi (Applied Food Research)
Saponins are amphipathic glycosides found in a wide variety of plants, including legumes, cereals, medicinal herbs, and marine organisms. They are divided into triterpenoid and steroidal saponins, which differ in chemical structures and biological activities. This review provides a comprehensive overview of the recent literature on the sources of saponins, their extraction methods, biological properties, and industrial applications, with a special focus on sustainable extraction methods and their industrial viability. Extraction techniques of saponins have evolved, transitioning from traditional methods such as maceration and reflux extraction to newer, more environmentally friendly methods, including ultrasound-assisted extraction, microwave-assisted extraction, supercritical fluid extraction, and deep eutectic solvent extraction. Fermentation-based techniques are also emerging as sustainable alternatives. Saponins possess remarkable anti-inflammatory, anti-tumor, and antioxidant properties, making them valuable in the management of chronic diseases such as diabetes, cardiovascular disorders, and cancer. Additionally, they enhance vaccine efficacy and bioavailability of drugs that act as adjuvants and nanocarriers. Their applications extend to cosmeceuticals as skin-friendly cleansers and anti-aging agents, to the food industry as natural preservatives and emulsifiers, and to agriculture, where their anti-fungal and immunomodulatory properties protect crops. Environmentally, saponins serve as biosurfactants aiding bioremediation and reducing greenhouse gas emissions. This review consolidates current knowledge on saponin biological activities, extraction technologies, and diverse applications, highlighting new opportunities for developing sustainable, multifunctional bioactive compounds for environmental, agricultural, and health sectors.